Acute ischaemia of the lower limb due to non-bacterial thrombotic endocarditis with recent venous thrombo-embolic disease as the initial manifestation of lung adenocarcinoma: a case report. Issue 11 (28th October 2021) - Polo, Julien; Raufast, Daniele; Cornand, Dimitri; Elias, Antoine
Abstract: Background: Non-bacterial thrombotic endocarditis is a rare condition. Optimal management is based on early diagnosis which remains difficult. Case summary: A 75-year-old male patient was admitted to the hospital with acute ischaemia of the left lower limb due to popliteal artery occlusion despite anticoagulation with rivaroxaban for pulmonary embolism diagnosed 2 weeks earlier. Transoesophageal echocardiography (TOE) showed a mobile vegetation with mild mitral valve regurgitation. Positron emission tomography (PET) scan did not show hyperfixation at the mitral valve but rather lymphadenopathy hyperfixation at different sites. Biopsy of a lymph node from Barety's space identified a bronchopulmonary adenocarcinoma. The outcome was favourable after popliteal artery thrombectomy and low-molecular-weight heparin treatment. The patient was referred to the department of onco-pneumology for further care. Discussion: Upon clinical presentation, the combination of an arterial and prior venous thrombotic event suggested that the origin could be either a patent foramen ovale (PFO) or a thrombosis from an underlying cancer. A transthoracic echocardiography and TOE excluded a PFO and demonstrated a mobile echogenic mass at the mitral valve site together with a mild regurgitation. The diagnosis of non-bacterial thrombotic endocarditis was suggested given the absence of clinical and biological infectious signs, negative blood cultures and serology for endocarditis, the presence of both arterial and venous thrombosis, as well as the presence of intra-thoracic lymphadenopathy hyperfixation on the PET scan for which a biopsy demonstrated lung adenocarcinoma.